Sea and Ocean as Fountains of Islanders’ Life and Creative Activities: An Ecological Perspective to Confront the Global Crisis - Konishi, Junko (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2023)
This paper considers the possibility of arts and performing arts to challenge the global crisis of the so called Anthropocene. It is the most recent period in Earth’s history when human activities significantly impacted the climate and ecosystems. This is exemplified by the case of Miyako Islands, the remote islands of Okinawa Prefecture, which illustrate how water has been fountains of islanders’ lives and creative activities is discussed. The theoretical background of this study includes nissology (island study) that has established the concept of an island, "aquapelago/aquapelagic" assemblages, the concept proposed by Hayward (2012), and ecomusicology. The "aquapelago" assemblages are integrated marine and terrestrial spaces for human beings, organisms and supernatural beings, such as the iconic imagined mer creature-the mermaid. Ecomusicology is defined as the study of music, culture, sound and nature in a period of environmental crisis. Although the underground dam was constructed to share the water with human beings, midzï-nu-nusï ru:gu, the gods living in the underground/underwater space, are believed with awe and reverence. This traditional and/or Indigenous Ecological Knowledge (TEK/IEK) concerned with water for living in Miyako Islands has been passed down from generation to generation through folklore, arts, and performing arts and remains at the historical sites and inspired creating performing arts. Interdisciplinary research on sea and ocean encourages artists and performers as well as scientists, technicians, and politicians to think and practice for Earth's sustainable future.